Perdagangan Orang (Trafficking) sebagai Pelanggaran Hak Asasi Manusia - Riswan Munthe (JUPIIS: JURNAL PENDIDIKAN ILMU-ILMU SOSIAL, 2015)
Human trafficking is garbage of civilization which is hard to be fought. This sentence provide an invasion for all that human trafficking is a common enemy. Human trafficking is often done by agent who has national even international network, has power, strong physically and arrogance. Due to the victim of human trafficking is the group in the lower class of economy and education. Generally the victim of human trafficking is everyone without exception. Since Indonesian independence, it is considered as the initial step for enforcing human rights nationally to break free from violation of human rights and violence, either physical violence, sexual, or psychological violence. This writing will deal with on the human trafficking as form of human right violation.